Reproductive performance of seahorse (Hippocampus comes) fed adult artemia bioencapsulated with fish liver oil. - Binh, Mac Nhu (2010.)
Reproductive performace f Hippocampus comes broodstock was evaluated as a effect of varying levels of incorporation of fish liver oil (FLO) bioencapsulated in Artemia. Eight different bioencapsulation lipid diets having 0%, 1%, 2%, 3%, 4%, 5%, 10% and 15% FLO supplemented with egg yolk, baker's yeast and vitamins were incorporated in adult Artemia and fed to seahorse (Hippocmpus comes) broodstocks. The results showed that bioencapsulation of adult Artemia with 5% fish liver oil improved the highly unsaturated fatty acid (HUFA) component in adult Artemia. The HUFA ranged from 5.42% (0%FLO) to 10.77% (5%FLO). When compared to other experimental treatments, seahorse fed adult Artemia bioencapsulated with 5% FLO significantly increased (P<0.05) the number of newborn seahorses (the highest number at 225). Feeding at 5% FLO also resulted in shorter periods between parturition (16 days) and longer survival of juvenile seahorse subjected to salinity stress tests, reaching up to 39 min, Juveniles of other treatments on the other hand had lower stress resistance with all juveniles dying within 26 to 34 min. These results were also significantly different among treatments (P<0.05)
Thesis (M. S. Fisheries - Aquaculture) - Institute of Aquaculture, College of Fisheries and Ocean Sciences, University of the Philippines Visayas, March 2010.
Keywords: Seahorse; Hippocampus comes; Artemia; Fish liver oil